Axillary Versus Femoral Arterial Cannulation During Repair of Type A Aortic Dissection? - Stamou, Sotiris C.; Gartner, Derek; Kouchoukos, Nicholas T.; Lobdell, Kevin W.; Khabbaz, Kamal; Murphy, Edward; Hagberg, Robert C. (AORTA, 2016)
Background: The goal of this study was to compare early postoperative outcomes and actuarial-free survival between patients who underwent repair of acute Type A aortic dissection with axillary or femoral artery cannulation.Methods: A total of 305 patients from five academic medical centers underwent acute Type A aortic dissection repair via axillary (n = 107) or femoral (n = 198) artery cannulation between January 2000 and December 2010. Major morbidity, operative mortality, and 5-year actuarial survival were compared between groups. Multivariate logistic regression was used to determine predictors of operative mortality, and Cox regression hazard ratios were calculated to determine predictors of long-term mortality.Results: Operative mortality was not influenced by cannulation site (16% for axillary cannulation vs. 19% for femoral cannulation, p = 0.64). In multivariate logistic regression analysis, hemodynamic instability (p < 0.001) and prolonged cardiopulmonary bypass time (>200 min; p = 0.05) emerged as independent predictors of operative mortality. Stroke rates were comparable between the two techniques (14% for axillary and 17% for femoral cannulation, p = 0.52). Five-year actuarial survival was comparable between the groups (55.1% for axillary and 65.7% for femoral cannulation, p = 0.36). In Cox regression analysis, predictors of long-term mortality were: age (p < 0.001), stroke (p < 0.001), prolonged cardiopulmonary bypass time (p = 0.001), hemodynamic instability (p = 0.002), and renal failure (p = 0.001).Conclusions: The outcomes of femoral versus axillary arterial cannulation in patients with acute Type A aortic dissection are comparable. The choice of arterial cannulation site should be individualized based on different patient risk profiles.
Keywords: Aortic dissection; Outcomes; Axillary cannulation; Femoral cammulation; Aorta; Dissection